The Amish: a concise introduction - Nolt, Steven M. (Young center books in Anabaptist and pietist studies, 2016)
Meet the Amish -- Amish roots -- Living the old order -- Community and church -- Rumspringa : Amish gone wild? -- Family and schooling -- Work and technology -- The Amish and their neighbors -- Amish images in modern america